Enhancing Students’ Writing Ability and Creativity through Project Based Learning on Greeting Card - Nurcahya Nurcahya; Ikariya Sugesti (Universitas PGRI Semarang, 2020)
This study focuses on the implementation of Project Based Learning (PjBL) in writing greeting card to enhance students’ writing ability and creativity. It is based on the classroom action research at the eighth grade of SMPN 1 Sumber, Cirebon, in the academic year of 2019/2020. The subject of the study were 32 students, they were 16 females and 16 males. This study was conducted into two cycles, and each cycle consisted of two meetings. The data were taken qualitatively and quantitatively. Qualitative data were taken from classroom observation, interview and pictures documentation. While quantitative data were taken from the writing test, including the students’ score on pre-test and post-test in each cycle. The findings showed that the use of PBL was able to enhance students’ writing ability. The implementation of PjBL strengthened students’ creativity since it enabled students to explore themselves while developing the greeting card. They were enthusiastic and active in participating during the teaching and learning process of writing. The findings showed that the students’ mean score in the pre-test was 67,8 and it increased to 94,15 in their post-test with the gain score 26,35, which indicated that the improvement was very significant.